APLIKASI FUNGI MIKORIZA ARBUSKULA DAN INTERVAL PENYIRAMAN TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN PAKCOY - Magdalena Sunarty Pareira; Maria Angelina Tuas; Kristina Irnasari Naikofi; Elfrida Knaofmone (Agros Journal of Agriculture Science, 2023)
The study was conducted to determine the amount of FMA, the influence and interaction of FMA as well as the right watering time with the drip irrigation system on the growth and yield of pakcoy plants. The study was conducted from November 2022 to January 2023, in the greenhouse of the Faculty of Agriculture, University of Timor. Using a complete factorial random design consisting of two factors, the first factor of arbuscula mycorrhizal fungi consists of three levels, namely 100% entisol soil without FMA, 40 grams of FMA inoculants and 60 grams of FMA inoculants while the second factor of watering arrangements consists of 3 levels, namely regular watering in the morning in the afternoon, two once in the morning and four in the morning in the afternoon,  repeated 4 times. The results showed that the administration of FMA 40 grams, FMA 60 grams and regular watering arrangements in the morning and evening gave the best results on the parameters of soil temperature, soil moisture content, soil pH, plant height, number of leaves, fresh weight of the plant and fresh weight of the roots.INTISARI  Penelitian dilakukan untuk mengetahui takaran FMA, pengaruh dan interaksi FMA serta waktu penyiraman yang tepat dengan sistem irigasi tetes terhadap pertumbuhan dan hasil tanaman pakcoy. Penelitian dilaksanakan pada bulan November 2022 sampai Januari 2023, di rumah kaca Fakultas Pertanian Universitas Timor. Menggunakan rancangan acak lengkap faktorial yang terdiri dari dua faktor, faktor pertama fungi mikoriza arbuskula terdiri dari tiga taraf yakni 100% tanah entisol tanpa FMA, 40 gram inokulan FMA dan 60 gram inokulan FMA sedangkan faktor kedua pengaturan penyiraman terdiri dari 3 taraf yakni penyiraman rutin pagi sore, dua sekali pagi sore dan empat hari pagi sore, diulang sebanyak 4 kali. Hasil penelitian menunjukkan dengan pemberian FMA 40 gram, FMA 60 gram dan pengaturan penyiraman rutin pagi dan sore memberikan hasil terbaik pada parameter suhu tanah, kadar lengas tanah, pH tanah, tinggi tanaman, jumlah daun, berat segar tanaman dan berat segar akar